Effect of replacing dried skim milk with soy products on function and morphology of the small intestine in nursery pigs - Jones, D.B.; Reddy, P.G.; Klemm, R.D.; Blecha, Frank; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty-six pigs (averaging 21 d of age and 11.8 lb) were used in a 7-d experiment to evaluate the effects of specially processed soy products on function and morphology of the small intestine. Treatments were: 1) corn-milk products control; 2, 3, 4, and 5) simple corn-based diets with either soybean meal, soy isolate2, soy concentrate3, or modified soy flour4 as the major protein source; 6) a high nutrient density diet (HNDD) containing 20% dried skim milk and 20% dried whey; 7, 8, and 9) the HNDD with soy isolate, soy concentrate, or modified soy flour plus lactose replacing 100% of the dried skim milk. Xylose absorption was determined from plasma collected on d 6 post-weaning. On d 7 post-weaning, serum was collected for determination of antisoy titers, and four pigs/trt were sacrificed for collection of tissues to determine villus height and crypt depth. The milk diet was more digestible than the other treatments, and the complex diets were more digestible than the simple diets. Nitrogen from soy isolate and concentrate was more digestible than N from soy flour in the simple diets. Pigs fed diets with the specially processed soy products had lower antisoy titers than pigs fed diets with soybean meal. However, diets with the specially processed soy products resulted in lower xylose absorptions than the diet with soybean meal. Pigs fed the corn-milk products control tended to have longer villi and lower crypt depths than pigs fed the other treatments. In conclusion, it appears that the specially processed soy products were better utilized than soybean meal but of lower nutritional value than milk products. Of the specially processed soy products, soy protein isolate had the greatest nutritional value in simple diets, but the soy products were of similar nutritional value in the complex diets.
Keywords: Swine; Starter; Peformance; SBM; Process; Soybean; Digestion